Pass-on Trade: Why do Firms Simultaneously engage in Two-Way Trade in the Same Varieties? - Jože P. Damijan; Jozef Konings; Sašo Polanec (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
This paper documents that a large fraction of trade flows at the firm level consists of simultaneous imports and exports in identical products, narrowly defined at the 8-digit product classification, which we call Pass-On Trade, POT. We use data on imports and exports at the firm?product level for Slovenian manufacturing firms in the period 1994-2008, to show that, on average, 70 percent of all exporting firms engage in POT. This corresponds to more than 50 percent of all exported products. Thus, imported products that are exported again by the same firm is a statistical regularity of trade of Slovenian manufacturing firms. We document that the use of POT is increasing in firm size, product diversification, multinational status as well as firm productivity and profitability. We offer and explore empirically a number of explanations for POT. Among possible explanations, we find evidence on the importance of firms' multinational networks and demand complementarities between firms' own and POT products. The latter confirms the theoretical explanations for ?Carry-Along Trade? (CAT) as developed by the recent work of Bernard et al (2010, 2012).
Keywords: R10; R15; 330; pass-on trade; multi-product firms; two-way trade; Industriegüteraußenhandel; Mehrproduktproduktion; Verarbeitendes Gewerbe; Slowenien